Effects of gremlin-2 on the transition of primordial follicles during early folliculogenesis in the human ovary. (August 2016) - Ikeda, Yuki; Hasegawa, Akiko; Tsubamoto, Hiroshi; Wakimoto, Yu; Kumamoto, Kanako; Shibahara, Hiroaki
Abstract: Objective: To investigate the localization and function of gremlin-2 during human ovarian folliculogenesis. Study design: Ovarian tissue from a gynecologic cancer patient was cultured in the presence or absence of gremlin-2 and then analyzed histologically. Growing follicles were counted by the microscopic observations of ovarian histological sections. Immunocytochemical staining was carried out to detect the expression of bone morphogenetic protein (BMP) 4 and phosphorylated Smad 1/5/8 (p-Smad 1/5/8). Results: Gremlin-2 was detected in human primordial, primary, and early growing follicles before culture. By day 4 of culture, the follicle growth rate in the presence of gremlin-2 (13.7%; 24/175) was significantly lower than that of the control (54.8%; 92/175; p  < 0.01). BMP4 expression was similar in the presence and absence of gremlin-2, whereas the p-Smad 1/5/8 signal was noticeably stronger in the absence of gremlin-2 in primordial and early-stage growing follicles. Conclusions: Gremlin-2 maintains the follicle store as primordial follicles by suppressing Smad 1/5/8 signaling in the human ovary. The data presented here provide potential insight into reproductive medicine for cases of intractable infertility, such as premature ovarian insufficiency and cancer survivors.